Reducing time delays in the management of ischemic stroke patients in Northern Italy. (15th July 2016) - Vidale, Simone; Arnaboldi, Marco; Bezzi, Giacomo; Bono, Giorgio; Grampa, Giampiero; Guidotti, Mario; Perrone, Patrizia; Salmaggi, Andrea; Zarcone, Davide; Zoli, Alberto; Agostoni, Elio; ,
Abstract: Background and purpose: Thrombolysis represents the best therapy for ischemic stroke but the main limitation of its administration is time. The avoidable delay is a concept reflecting the effectiveness of management pathway. For this reason, we projected a study concerning the detection of main delays with following introduction of corrective factors. In this paper we describe the results after these corrections. Materials and methods: Consecutive patients admitted for ischemic stroke during a 3-months period to 35 hospitals of a macro-area of Northern Italy were enrolled. Each time of management was registered, identifying three main intervals: pre-hospital, in-hospital and total times. Previous corrective interventions were: 1.increasing of population awareness to use the Emergency Medical Service (EMS); 2.pre-notification of Emergency Department; 3.use of high urgency codes; 4.use of standardised operational algorithm. Statistical analysis was conducted using time-to-event analysis and Cox proportional hazard regression. Results: 1084 patients were enrolled. EMS was alerted for 56.3% of subjects, mainly in females and severe strokes (p < 0.001). Thrombolytic treatment was performed in 4.7% of patients. Median pre-hospital and in-hospital times were 113 and 105 min, while total time was 240. High urgency codes at transport contributed to reduce pre-hospital and in-hospital time (p < 0.05). EMS use and high urgency codes promoted thrombolysis. Treatment within 4.5 hours from symptom onset was performed in 14% of patients more than the first phase of study. Conclusions: The implementation of an organizational system based on EMS and concomitant high urgency codes use was effective to reduce avoidable delay and to increase thrombolysis.